(untitled) (Research, Society and Development, 2023)
Objective: to trace the clinical and epidemiological profile of pregnant women and internal puerperal women in a COVID-19 intensive care unit in a high complexity maternity hospital in the city of Teresina-PI. Methods: this is a quantitative, descriptive, retrospective study of medical records review conducted in a maternity hospital located in the city of Teresina-PI. Medical records of pregnant women with clinical or serological diagnosis of COVID-19 were included. Medical records with many incomplete data (above 20), patients without a diagnosis of COVID-19 and symptoms appeared after delivery were excluded. Results: The total sample of this study consisted of 43 medical records of patients who met the established criteria, most of them women aged 18 to 30 years (60.4%; N=26), with a weight greater than 65kg (60.4%; N=26), multi-gestas (55.8%; N=24), who performed prenatal consultations (88.3%; N=38) and presented at least one intercorrence in pregnancy (67.4%; N=29). The most reported clinical manifestations were dyspnea (95.3%; N=42) and cough (81.3%; N=35). In addition, the research reveals a high rate of preterm delivery (80%; N=20) and cesarean (100%; N=25). 69.7% (N=30) of the sample required ventilatory support. It is necessary to conduct further studies to understand the true profile of this public and understand the other consequences that the disease brings to pregnant women.